The debtor’s delay: legal implications of obligation breach - Orúe Cruz , José René (Scientific journal of social studies, 2024)
The recognition and analysis of the different theories developed in Latin America on the institution of the mora; we identify the system that embraces our Civil Code. Article 1859 of the Civil Code is analyzed, which delimits the figure of the debtor’s default, the analysis includes incorporating different expert criteria; as well as resolutions of the Supreme Court of Justice that have been contested with the provisions of the law and the contributions of the doctrine. The study also incorporates the analysis of commercial defaults. It is concluded that the Civil Code is based on the recognition of the default after interpellation of the debtor; but in a sui generis way, stipulating exceptions; recognizing that in bilateral services of simultaneous performance, it will be in default when the other party does not comply with what is due.